Exploring factors contributing to school improvement in South African secondary schools in the free state province - Makoelle, Tsediso (International Journal of Educational Sciences, 2014)
Since the advent of the new educational dispensation in 1994, the South African National Department of education has embarked on a process of enhancing the improvement of pass-rates in secondary schools. However, despite these efforts the process has not been very smooth as some schools have not improved or least show signs of the improvement of their performances. This paper therefore explores factors contributing to school improvement in secondary schools...
Keywords: Curriculum; Leadership; management; School Effectiveness; teaching